2021
DOI: 10.1111/jipb.13174
|View full text |Cite
|
Sign up to set email alerts
|

OsMKKK70 regulates grain size and leaf angle in rice through the OsMKK4‐OsMAPK6‐OsWRKY53 signaling pathway

Abstract: Grain size and leaf angle are key agronomic traits that determine final yields in rice. However, the underlying molecular mechanisms are not well understood. Here we demonstrate that the Oryza sativa Mitogen Activated Protein Kinase Kinase Kinase OsMKKK70 regulates grain size and leaf angle in rice. Overexpressing OsMKKK70 caused plants to produce longer seeds. The osmkkk62/70 double mutant and the osmkkk55/62/70 triple mutant displayed significantly smaller seeds and a more erect leaf angle compared to the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…In addition, oswrky53 mutant plants have decreased brassinosteroid (BR) sensitivity, whereas overexpressing OsWRKY53 leads to hypersensitivity to BR, and the phosphorylation of OsWRKY53 by OsMPK6 is required for its function in regulating BR responses. Recently, the same laboratory also demonstrated that OsMKKK70, together with OsMKKK55 and OsMKKK62 (orthologs of Arabidopsis MPKKK15/16/17/18), regulate grain size and leaf angle in rice through the OsMKK4–OsMAPK6–OsWRKY53 signaling module (Liu et al, 2021b). Compared to the wild type, the osmkkk62/70 double and osmkkk55/62/ 70 triple mutant plants set much smaller seeds and have a more erect leaf angle, whereas the overexpression of OsMKKK70 leads to bigger/longer seeds.…”
Section: Mapk Cascades In Plant Growth and Developmentmentioning
confidence: 99%
“…In addition, oswrky53 mutant plants have decreased brassinosteroid (BR) sensitivity, whereas overexpressing OsWRKY53 leads to hypersensitivity to BR, and the phosphorylation of OsWRKY53 by OsMPK6 is required for its function in regulating BR responses. Recently, the same laboratory also demonstrated that OsMKKK70, together with OsMKKK55 and OsMKKK62 (orthologs of Arabidopsis MPKKK15/16/17/18), regulate grain size and leaf angle in rice through the OsMKK4–OsMAPK6–OsWRKY53 signaling module (Liu et al, 2021b). Compared to the wild type, the osmkkk62/70 double and osmkkk55/62/ 70 triple mutant plants set much smaller seeds and have a more erect leaf angle, whereas the overexpression of OsMKKK70 leads to bigger/longer seeds.…”
Section: Mapk Cascades In Plant Growth and Developmentmentioning
confidence: 99%
“…In rice plants, the OsMKKK70-OsMKK4-OsMPK6 cascade regulates grain size and leaf angle [ 60 ]. In this signaling cascade, OsMKKK70 (a MEKK-like MAPKKK) shows in vitro kinase activity and physically interacts with its downstream kinase, OsMKK4, in yeast and tobacco cells, but does not phosphorylate OsMKK4 ( Table 2 ).…”
Section: Uncanonical Regulation Of Mapk Cascades By Mapkkksmentioning
confidence: 99%
“…As OsMKKK70 does not interact with OsMPK6, it is unlikely that OsMKKK70 functions as a scaffold protein tethering both OsMKK4 and OsMPK6 to promote OsMPK6 phosphorylation by OsMKK4. Thus, whether the OsMKKK70 kinase activity is involved in the regulation of the OsMKK4-OsMPK6 cascade and how OsMKK4-OsMPK6 is activated have to be further studied [ 60 ].…”
Section: Uncanonical Regulation Of Mapk Cascades By Mapkkksmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, banana MaMPK14 enhanced MaBZR1/2-mediated transcriptional repression of fruit ripening-related genes [ 9 ], while MaMPK6–3 phosphorylates MabZIP21, which in turn increases its transcriptional activation of ripening-associated genes [ 10 ]. Recently, rice OsMKKK70 participates in the OsMKK4-OsMAPK6-OsWRKY53 signaling pathway to regulate leaf angle and grain size [ 11 ]. FaMAPK5 and FaMAPK10 are related to ABA-mediated fruit ripening in strawberry [ 12 ].…”
Section: Introductionmentioning
confidence: 99%